2009
DOI: 10.1097/mcg.0b013e31818be17c
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hepatic Fibrosis In Patients With Chronic Hepatitis C

Abstract: The present study indicated that elderly, longer duration of HCV infection, obesity, and history of diabetes mellitus are independent clinical parameters associated with advanced fibrosis, whereas elevated AST, alpha fetoprotein, and presence of grade 2 and 3 steatosis are independent laboratorial parameters associated with stage 3 and 4 fibrosis in patients with CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 48 publications
5
25
3
1
Order By: Relevance
“…The progression of chronic hepatitis is highly variable among individuals as a result of several factors including quasispecies diversity, viral genotype, gender, age at infection, alcohol intake, diabetes, and duration of infection [48,49]. However, these viral, demographic, and environmental factors account for only a small proportion of the variability [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The progression of chronic hepatitis is highly variable among individuals as a result of several factors including quasispecies diversity, viral genotype, gender, age at infection, alcohol intake, diabetes, and duration of infection [48,49]. However, these viral, demographic, and environmental factors account for only a small proportion of the variability [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…3,25,26 One study has suggested that antioxidant defense mechanism deteriorates with age, and leaves the liver vulnerable to oxidative stress. 27 Our finding was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, overt diabetes may develop earlier than in HCV negative persons [103] . Glucose metabolism is altered by HCV at early stages of the infection, leading to insulin resistance [86] which, when combined with type 2 diabetes, accelerates liver disease progression [86,88] and reduces the response to combined pegylated interferon (PEGIFN) with Ribavirin (RBV) [104,105] , although the res ponse to regimens containing directacting antiviral (DAA) does not seem to be affected by glucose metabolism alterations [106] . Other extrahepaticassociated diseases include porphyria cutanea tarda, lichen planus, necrolytic acral erythema, sialadenitis, sicca syndrome, and autoimmune thyroiditis [96] .…”
Section: Extrahepatic Manifestationsmentioning
confidence: 99%
“…Tobacco inhalation is associated with liver affection, and consequently with increased fibrosis score [82] , whereas coffee has a protective role against fibrosis [83] and HCC [84] . Steatosis [66,85] , insulin resistance [86,87] , and type 2 diabetes [88,89] are associated with disease progression and the possibility of HCC. Iron overload is related to severe fibrosis [90] .…”
Section: Chronic Hcv -Disease Progressionmentioning
confidence: 99%